Development of a Manychat Based Chatbot for Automated Customer Support System (International Journal of Latest Technology in Engineering Management & Applied Science, 2025)
Abstract: In today’s fast-paced digital age, customer service demands have evolved with customers expecting prompt and accurate responses to their inquiries and request. However, traditional customer service methods often struggle to meet these expectations. The rise of artificial intelligence and natural language processing technologies present an opportunity to address these challenges through the development of intelligent chatbot system. This research aimed to develop and train a chatbot system using ManyChat that can promptly, accurately, and effectively address basic customer inquiries and handle simple request.The methodology employed in this research involved a multi stage approach. Firstly, requirement analysis was conducted through stakeholder meetings, user feedback, and scope definition. Next, the design phase utilized user flow mapping to visualize the customer journey from the initial interaction to issue resolution. The chatbot was then developed on ManyChat platform. Following development, testing, and refinement were performed based on feedback. The performance of the chatbot was evaluated after receiving feedback from multiple users using user satisfaction, task completion rate, and ability to resolve customer inquiries.The results of the evaluation reveal that the developed chatbot has a value of 92%, 87%, and 92% for user satisfaction, task completion rate, and ability to resolve customer inquiries respectively.The findings underscore the ManyChat based chatbot efficiency as a reliable means of providing prompt and accurate responses to customer inquiries. This research proves how ManyChat can be used to build intelligent and scalable chatbot that can be tailored to specific business requirement, and thereby improving the customer experience.